Toxic Properties of Plastics in Fire and Their Impact on the Environment and Human Health - Martin Hrinko; Katerina Orlikova (Communications - Scientific letters of the University of Zilina, 2011)
The article describes and analyses toxic substances produced during a combustion of plastics which affect human health. Accidents and emergencies resulting from the combustion of plastic materials occur very often during the industrial production and technological processes. The authors illustrate this fact using the most recent example – the fire in the manufacturing and logistics premises in Chropyne, the Czech Republic, during which the professional as well as volunteer firefighters and the specialized fire rescue service units were employed.